ASSESSMENT OF THE SITUATION OF USE OF TYPE 2 DIABETES IN OUTCOME PATIENTS AT NAM DINH PROVINCIAL HOSPITAL IN OCTOBER 2021 (Vietnam Journal of Community Medicine, 2022)
Objectives: Describe the use of drugs to treat type 2 diabetes by outpatients at Nam Dinh GeneralHospital in October 2021.Subjects and methods: A cross-sectional descriptive study on 1599 prescriptions of patientsundergoing examination and treatment for type 2 diabetes.Results: The prevalence of the disease between men and women was 49.4/50, 6%, the age group mostaffected is from 61 to 79. The monotherapy regimen is quite commonly used, accounting for 58.7%,the drug treatment: insulin is used the most, accounting for 52.6%, Metformin and sulfonylurea isthe most commonly used combination, accounting for 21.2%. Most of the pairs interact at a cautiouslevel, monitoring and monitoring blood glucose levels to adjust the dose to suit the clinical responseof the patient.
Keywords: Hyperglycemia, target blood sugar, antidiabetic drugs.